Pengembangan Lembar Kerja Peserta Didik (LKPD) pada Pembelajaran Tematik di Kelas V SD Islam Terpadu NU Tanjung Baru T. A. 2022-2023 - Rahmasari, Rizki; Harahap, Syarifah Ainun; Herdyana, Thessa (Medan Resource Center, 2024)
This study aims to address the lack of development of thematic LKPD (Student Worksheets) at NU Tanjung Baru Integrated Islamic Elementary School. Utilizing the Research and Development (R&D) methodology, this research followed ten structured stages: identifying potential problems, data collection, product design, product validation, design revision, product trial, product revision, usage trial, further revision, and mass production. Expert assessments from material, media, and language reviewers yielded scores in the